2021
DOI: 10.1007/s41061-020-00318-2
|View full text |Cite
|
Sign up to set email alerts
|

Reviews on Biological Activity, Clinical Trial and Synthesis Progress of Small Molecules for the Treatment of COVID-19

Abstract: COVID-19 has broken out rapidly in nearly all countries worldwide, and has blossomed into a pandemic. Since the beginning of the spread of COVID-19, many scientists have been cooperating to study a vast array of old drugs and new clinical trial drugs to discover potent drugs with anti-COVID-19 activity, including antiviral drugs, antimalarial drugs, immunosuppressants, Chinese medicines, M pro inhibitors, JAK inhibitors, etc. The most commonly used drugs are antiviral compounds, antimalarial drugs and JAK inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 176 publications
(186 reference statements)
0
25
0
Order By: Relevance
“…As ultrasound irradiation has dramatically accelerated organic reactions, sonochemical synthesis has gained considerable attention in recent years [46], and diverse transformations have been performed using ultrasound [47,48]. For example, Kusumaningsih et al prepared dimeric 2,4-diacetyl phloroglucinol in a 95% yield after sonication for 30 min at 60º [32].…”
Section: Resultsmentioning
confidence: 99%
“…As ultrasound irradiation has dramatically accelerated organic reactions, sonochemical synthesis has gained considerable attention in recent years [46], and diverse transformations have been performed using ultrasound [47,48]. For example, Kusumaningsih et al prepared dimeric 2,4-diacetyl phloroglucinol in a 95% yield after sonication for 30 min at 60º [32].…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing SARS studies revealed some inhibition approaches with micromolar to nanomolar activity [ 87 ]. Variable segments of the virus can be the target for inhibition such as 3CLP, PLP, RNA-dependent RNA polymerase (RdRp), and the 50–30 helicase, E protein (Orf4), M protein (Orf6), and N protein (Orf9) [ 89 ].…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
“…The problem stimulates innovations and drives, in part, the development of both medicinal chemistry and modern organic synthesis. The urgency of the problem has prompted chemical community to perform in silico analysis the affi nity of compounds in the existing libraries for the known SARS-CoV2 targets [2][3][4][5][6][7] and urgently consider the possibility of repurposing existing drugs [3,4,[8][9][10][11][12][13][14][15][16][17]. In view of the sharply increased global demand, there is an urgent need for the development and scaling of new methods of synthesis, as well as costeffective technological solutions for the production of antiviral pharmaceutical substances [18][19][20].…”
Section: Doi: 101134/s107042802105002xmentioning
confidence: 99%